Clinical predictors of nephrotoxicity associated with teicoplanin: Meta‐analysis and meta‐regression. Issue 1 (18th November 2021) - Hirai, Toshinori; Hosohata, Keiko; Ogawa, Yukari; Iwamoto, Takuya
Abstract: Teicoplanin is a glycopeptide antibiotic against methicillin‐resistant Staphylococcus aureus infections. However, the impact of clinical characteristics on nephrotoxicity associated with teicoplanin has not been determined. This meta‐analysis aimed to investigate the relationship between clinical characteristics and nephrotoxicity associated with teicoplanin. We identified clinical research published from January 1975 to June 2021 using PubMed, Cochrane Library, and Scopus, which described the nephrotoxicity associated with teicoplanin. Meta‐analysis determined the incidence of nephrotoxicity. Using meta‐regression analysis, we evaluated the impact of clinical characteristics on outcomes. Of the 567 articles, eight articles including 634 patients were analysed. The overall incidence of nephrotoxicity associated with teicoplanin was 11.0% (95% confidence interval: 8.0–13.0) for the fixed‐effect model. Additionally, patients with >65 years had a high trend for the risk of nephrotoxicity compared to those with ≤65 years (>65 years; 12.0% [95% confidence interval: 9.0–15.0] vs. ≤65 years; 7.0% [95% confidence interval: 3.0–12.0], p  = 0.09) for the fixed‐effect model. Meta‐regression analysis demonstrated that only serum albumin level negatively correlated with the risk of nephrotoxicity ( y  = −17.0 x  + 56.7, r  = 0.74, p  = 0.01). This meta‐analysis ascertained that hypoalbuminemia leads to nephrotoxicity associated with teicoplanin.